Mapping the research trends of astrocytes in stroke: A bibliometric analysis - Ding, Zhibin; Jiang, Nan; Yang, Ting; Han, Hongxia; Hou, Miaomiao; Kumar, Gajendra; Wu, Yige; Song, Lijuan; Li, Xinyi; Ma, Cungen; Su, Yanbing (Frontiers in Cellular Neuroscience, 2022)
Background Stroke, including ischemic stroke and hemorrhagic stroke, possesses complex pathological mechanisms such as neuroinflammation, oxidative stress and blood-brain barrier damage. Astrocyte functions have been reported during injury, neuroprotection and cell crosstalk. It plays a key role in exacerbating stroke injury, promoting neurological repair and enhancing neuroregeneration. Aim This holistic bibliometric analysis aimed to provide a general overview of the recent advancement and the hotspots in the field of stroke and astrocyte from 2001 to 2021. Materials and methods Publications between 2001 and 2021, related to stroke and astrocyte were retrieved from the Web of Science (WOS) and analyzed in Gephi and VOSviewer. Results In total, 3789 documents were extracted from the WOS databases. The publications showed stable growth since 2001. The United States and China were the most prolific countries and University of California San Francisco and Oakland University were the most influential institutes. The top four most productive journals were Brain Research, Journal of Cerebral Blood Flow and Metabolism, Glia and Journal of Neuroinflammation. Keywords frequency and co-occurrence analysis revealed that the topics related to “micro-RNA”, “toll like receptor”, “neuroinflammation”, “autophagy” and “interleukin” were research frontiers. The field of stroke and astrocyte focused on several aspects, such as the role of astrocytes in the treatment of stroke, metabolic changes in astrocytes, the protective role of apoptosis in astrocytes after oxidative stress injury and neurovascular units. Conclusion This comprehensive bibliometric study provides an updated perspective on the trend of research associated with stroke and astrocyte. It will benefit scientific community to identify the important issues, future directions and provide a novel understanding of stroke pathophysiology, hotspots and frontiers to facilitate future research direction.